Peran Keterlibatan Ayah dalam Pengasuhan dengan Konsep Diri Remaja Tunadaksa - Mutia, Fatimah; Andayani, Tri Rejeki (UIN Sunan Kalijaga, 2023)
One of the problems that often faced by the teenagers with physical disabilities is the negative self-concept. Self-concept is a description of a person affected by the environment. The negative self-concept could lead the teenagers into a higher level of juvenile delinquency. Father, as one of the family members has an important role in shaping self-concept on teenagers. Teenagers with adequate attention of a father would tend to feel loved and worth that could lead them to shape a positive self-concept. The purpose of this quantitative-correlational was to determine the role of father involvement in self-concept of teenagers with physical disabilities. The respondents of this research were teenagers with physical disabilities aged 13 – 19 years old with father in total 53 respondents. Sampling technique used in this research was non-probability by using purposive sampling. The instrument used was Father Involvement Scale (rxx’=0,904) and Self-Concept Scale (rxx’=0,930). Data analysis technique was simple linier regression analysis. The result of study showed that there was significant correlation between father involvement in self-concept of teenagers with physical disabilities (R=0,452, p<0,05). Known the value of R2 was 0,204,. It means values the role father involvement in self-concept of teenagers with physical disabilities is 20,4%. Salah satu permasalahan yang sering dijumpai remaja tunadaksa adalah konsep diri negatif. Konsep diri merupakan gambaran mengenai dirinya sendiri yang dipengaruhi oleh lingkungan. Konsep diri negatif dapat membawa remaja pada tingkat kenakalan yang tinggi. Ayah merupakan salah satu anggota dari keluarga yang berperan dalam membentuk konsep diri remaja. Remaja yang mendapat perhatian dari ayahnya akan merasa disayang, berharga, dan mendorong remaja membentuk konsep diri positif. Penelitian kuantitatif-korelasional ini bertujuan untuk mengetahui peran keterlibatan ayah dalam pengasuhan dengan konsep diri remaja tunadaksa. Responden dalam penelitian ini remaja tunadaksa berusia 13-19 tahun yang memiliki ayah dengan jumlah 53 responden. Teknik pengambilan sampel pada penelitian ini adalah non-probability dengan menggunakan purposive sampling. Instrumen yang digunakan dalam penelitian ini adalah Skala Keterlibatan Ayah dalam Pengasuhan (rxx’=0,904) dan Skala Konsep Diri (rxx’=0,930). Teknik analisis data dalam penelitian ini adalah analisis regresi linier sederhana. Hasil dari penelitian ini menunjukkan adanya hubungan signifikan antara keterlibatan ayah dalam pengasuhan dengan konsep diri remaja tunadaksa (R= 0,452, p< 0,05). Diketahui nilai R2 (R Square) sebesar 0,204, artinya nilai peran keterlibatan ayah dalam pengasuhan terhadap konsep diri remaja tunadaksa adalah 20,4%.